Analysis of Mass Transfer Efficiency in a Compact Wet Scrubber - Pietro Giustacori; Elisabetta Brunazzi (Chemical Engineering Transactions, 2025)
This study investigates a compact wet scrubber, a versatile pollution control device designed to efficiently remove particulates and contaminant gases from industrial gas streams. The system features a nozzle integrated into a vertical channel as its core element. The nozzle allows the scrubbing liquid to be injected countercurrently to the descending gas flow. This configuration is intended to create a highly turbulent foam zone, that can significantly enhance mass transfer efficiency. The lack of internal components provides flexibility in handling high-flow gas streams with varying particulate concentrations, making it potentially suitable for a variety of industrial applications. Despite the growing interest in this type of compact scrubber for specific industrial sectors, there is limited knowledge about its design and performance. To address this gap, the present study introduces an experimental setup for characterizing the performance of the compact scrubber. Gas pressure drop measurements across the liquid jet were used as a key tool to identify the scrubber’s operating window. Additionally, absorption tests of volatile organic compounds with different solubilities were conducted to assess mass transfer performance. Key parameters, including overall mass transfer coefficient and absorption efficiency, were determined for various gas and liquid flow rates. The results showed remarkable absorption efficiencies of up to 90%, with gas-liquid contact times of less than 1 second.